Anti-competitive conduct, in-house R&D, and growth - Volker Grossmann; Thomas M. Steger (Center for Economic Studies and ifo Institute (CESifo), 2007)
Incumbent firms have two basic possibilities to improve their competitive position in the product market: investment in R&D and the creation of entry barriers to the disadvantage of potential rivals, e.g. through lobbying activities, campaign contributions, bribes or the adoption of incompatible technologies. This paper proposes a simple oligopoly model which raises the possibility that such anti-competitive conduct and R&D investment are complementary activities for incumbents. Consequently, an institutional framework or technological possibilities which encourage anti-competitive conduct, although impeding entry of potential rivals and accentuating standard oligopoly distortions, may foster R&D-based growth and welfare. However, this outcome is less likely if entrants exert technological spillover effects, e.g. through foreign direct investment. Stronger protection of intellectual property rights, although triggering anti-competitive conduct and thereby impeding market entry as well, is more likely to foster economic growth.
Keywords: L13; O31; O40; 330; Wettbewerbsbeschränkung; Markteintritt; Industrielle Forschung; Interessenpolitik; Oligopol; Neue Wachstumstheorie; Wissenstransfer; Theorie